Comparison between Conventional Blind Injections and Ultrasound-Guided Injections of Botulinum Toxin Type A into the Masseter: A Clinical Trial - Hyungkyu Bae; Jisoo Kim; Kyle K. Seo; Kyung-Seok Hu; Seong-Taek Kim; Hee-Jin Kim (Toxins, 2020)
The aim of the study was to propose a more efficient and safer botulinum toxin type A (BoNT-A) injection method for the masseter by comparing the conventional blind injection and a novel ultrasonography (US)-guided injection technique in a clinical trial. The 40 masseters from 20 healthy young Korean volunteers (10 males and 10 females with a mean age of 25.6 years) were included in this prospective clinical trial. The BoNT-A (24 U) was injected into the masseter of each volunteer using the conventional blind and US-guided injection techniques on the left and right sides, respectively, and analyzed by US and three-dimensional (3D) facial scanning. One case of PMB (paradoxical masseteric bulging) was observed on the side where a conventional blind injection was performed, which disappeared after the compensational injection. The reduction in the thickness of the masseter in the resting state differed significantly at 1 month after the injection between the conventional blind injection group and the US-guided injection group by 12.38 ± 7.59% and 17.98 ± 9.65%, respectively (t(19) = 3.059, p = 0.007). The reduction in the facial contour also differed significantly at 1 month after the injection between the conventional blind injection group and the US-guided injection group by 1.95 ± 0.74 mm and 2.22 ± 0.84 mm, respectively (t(19) = 2.908, p = 0.009). The results of the study showed that the US-guided injection method that considers the deep inferior tendon by visualizing the masseter can prevent the PMB that can occur during a blind injection, and is also more effective.